2011
DOI: 10.1007/s00277-010-1150-7
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system (CNS) relapse in diffuse large B cell lymphoma (DLBCL): pre- and post-rituximab

Abstract: Central nervous system (CNS)-directed prophylactic intrathecal (IT) therapy is indicated in patients with Burkitt and acute lymphoblastic lymphoma. Its role in diffuse large B cell lymphoma (DLBCL), a heterogeneous subtype, is less well defined. While addition of rituximab to standard cyclophosphamide-hydroxydaunorubicin-oncovin-prednisone (CHOP) chemotherapy (R-CHOP) has improved the outcomes of DLBCL patients, its role in reducing CNS relapse is unclear. We aim to (1) evaluate the clinical risk factors predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 18 publications
4
99
1
5
Order By: Relevance
“…11,12 In this paper, we report the experience of 2 centers in CNS prophylaxis with liposomal cytarabine in patients with DLBCL and PMBCL treated with R-CHOP. Liposomal cytarabine (Depocyte®, Mundipharma International Limited) is a sustained-release formulation of cytarabine developed for intrathecal administration, ensuring prolonged cytotoxic drug concentrations of cytarabine in the cerebrospinal fluid (CSF).…”
mentioning
confidence: 99%
“…11,12 In this paper, we report the experience of 2 centers in CNS prophylaxis with liposomal cytarabine in patients with DLBCL and PMBCL treated with R-CHOP. Liposomal cytarabine (Depocyte®, Mundipharma International Limited) is a sustained-release formulation of cytarabine developed for intrathecal administration, ensuring prolonged cytotoxic drug concentrations of cytarabine in the cerebrospinal fluid (CSF).…”
mentioning
confidence: 99%
“…However, CNS recurrence occurs in 1.1% to 10.4% of patients, and the prognosis remains poor [2]. Whether the addition of rituximab decreases the risk of CNS recurrence for systemic DLBCL has not yet been proven [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have suggested that a high-dose intravenous rituximab infusion or intrathecal rituximab infusion may be an effective treatment option [13], although the clinical safety of such treatments has not been yet been confirmed. In order to prevent CNS recurrence of DLBCL, intrathecal chemotherapy such as MTX and cytarabine is currently performed in many institutions, although its efficacy has been controversial [2,[14][15][16][17][18]. Kim et al described the treatment of 73 DLBCL patients with secondary CNS involvement in 11 institutions in Korea [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16] To address some of these limitations, Schmitz et al developed a 6-point score from 2164 patients treated on prospective German studies and validated in 1597 patients with DLBCL treated with R-CHOP in the British Columbia Cancer Agency (BCCA) Lymphoid Malignancies Database. 6 The components of the score were the International Prognostic Index (IPI) factors: age .…”
Section: How I Identify Patients At Increased Risk For Cns Relapsementioning
confidence: 99%